Six months interim analysis of the phase 2 study of AL001 in frontotemporal dementia patients carrying a granulin mutation. (31st December 2021) - Jackson, Sam; Yeh, Felix L; Ward, Michael; Rhinn, Herve; Huang, Julie Y.; Pappalardo, Jenna L.; Liao, Yijie; Hagey, Mackenzie; Long, Hua; Paul, Robert
Abstract: Background: Frontotemporal dementia (FTD) is a rare, early‐onset form of dementia and loss‐of‐function mutations in the progranulin gene ( GRN) are a common cause of familial FTD. In the brain, progranulin (PGRN) is a key regulator of microglia activity and lysosomal function. AL001 is a human monoclonal IgG1 antibody that blocks and downregulates Sortilin, a receptor in the key degradation pathway of PGRN, and is being developed by Alector for the treatment of carriers of GRN mutations causative of FTD (FTD‐ GRN ). Restoring PGRN levels may be an effective therapeutic approach in FTD, and AL001 was shown to normalize CSF PGRN levels in GRN mutation carriers in a Phase 1 study. Method: INFRONT‐2 is an open‐label, Phase 2 study in GRN mutation carriers to investigate the safety, tolerability, pharmacokinetics (PK), and pharmacodynamics (PD) of AL001 administered intravenously every four weeks. Lumbar punctures and MRI scans were performed at baseline and every 6 months. Clinical assessments were done every 3 months. Fluid biomarkers in plasma and CSF were analyzed using multiple platforms. Result: Preliminary results demonstrated that AL001 was generally safe and well tolerated in FTD‐ GRN participants in INFRONT‐2. Chronic dosing led to a sustained increase in PGRN levels to the normal range in FTD‐ GRN carriers. Preliminary CSF biomarker data related to key aspects of FTD‐ GRN pathophysiology, namely changes in levels of lysosomal proteins and markers of inflammation, will be presented for FTD‐ GRN participants who received AL001 for 6 months. In addition, updated biomarker data related to neurodegeneration will be presented. Conclusion: There is a high unmet need for effective therapies in FTD. AL001 is being developed for the treatment of FTD‐ GRN to reduce the rate of neurodegeneration by increasing levels of PGRN and disrupting the pathophysiologic cascade associated with FTD‐ GRN . INFRONT‐3 is an ongoing, pivotal Phase 3 study to evaluate if AL001 can slow or stop disease progression in carriers of GRN mutations.